Leaping ability and body composition in rhythmic gymnasts for talent identification - Di Cagno, A.; Baldari, C.; Battaglia, C.; Brasili, P.; Merni, F.; Piazza, M.; Toselli, S.; Ventrella, A. R.; Guidetti, L. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. Aim of this study was to investigate leaping ability and morphological characteristics in rhythmic gymnastics, in order to verify which parameters are useful indicators for the talent identification. Methods. Twenty-five national gymnasts of international level (age 14.7±2.2 years) underwent three testing sessions: anthropometric measurements, vertical jumps (counter movement jump and hopping test), and three technical split leaps with stretched legs (SL), with ring (RG) and with back bend of the trunk (BBT). Results. Elite had significantly different values (P<0.05) of stature (1.65±0.03 vs 1.55±0.09 m), thigh length (0.42±0.03 vs 0.39±0.02 m) and FFM(42.42±2.81 vs 35.84±5.66 kg) compared to sub-elite. The height of hopping test was significantly higher in elite than sub-elite gymnasts (0.34±0.05 vs 0.27±0.04 m; P<0.05), but no significant differences in counter movement jump between two groups were found. Ground contact time of hopping test was significantly correlated (P<0.01) with SL (r=0.613), RG (r=0.632), and BBT (r=0.542) values. By multiple regression analysis, among anthropometric and vertical jump variables, the hopping ground contact time was the strongest predictor of ground contact time of the three technical leaps (SL, RG, BBT) accounting for 26-37% of variance. Conclusion. Some anthropometric measurements are good indicators for the better performance in rhythmic gymnastics. Level of muscle compliance (stiffness) evaluated by hopping test is a good parameter for athletes selection and for monitoring leaps training.